2001
DOI: 10.1177/004728750104000102
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Travel-Related Behaviors of the Mobility-Disabled Consumer

Abstract: Few consumer groups have greater potential and are more ignored than the disabled. Consisting of 50 million individuals in the United States, with discretionary income of over $200 billion, this largest of all minority groups has been viewed by many tourist businesses as a source of confusion, requiring extra expenditures on ramps, specially fitted rooms, and the loss of prime parking. This article offers new insights into the possibilities associated with the disabled, including general trends and need sets. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
137
0
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(172 citation statements)
references
References 14 publications
23
137
0
12
Order By: Relevance
“…Yet, for the most part, disability is still treated as a single dimensional construct. Much of the early research in this area found little differentiation between the dimensions of access, except for a few notable exceptions (Woodside & Etzel, 1980;Murray & Sproats, 1990;Darcy, 1998;Burnett and Bender-Baker, 2001). Disability is a multidimensional construct, with each dimension having its own access requirements that are significantly different to each other (Darcy, 1998;2010).…”
Section: Disability Dimensions Of Access and Support Needsmentioning
confidence: 99%
“…Yet, for the most part, disability is still treated as a single dimensional construct. Much of the early research in this area found little differentiation between the dimensions of access, except for a few notable exceptions (Woodside & Etzel, 1980;Murray & Sproats, 1990;Darcy, 1998;Burnett and Bender-Baker, 2001). Disability is a multidimensional construct, with each dimension having its own access requirements that are significantly different to each other (Darcy, 1998;2010).…”
Section: Disability Dimensions Of Access and Support Needsmentioning
confidence: 99%
“…Although studies on disabilities and tourism generally centre on people with physical disabilities (Burnett and Baker, 2001;Daniels et al, 2005;Bi et al, 2007;Blichfeldt and Nicolaisen, 2011;Hua et al, 2013), other studies focus on sensory impairment (Poria et al, 2009;Yau et al, 2004). Daniels et al (2005) analysed travel constraints and the negotiation strategies of people with physical disabilities, while Hua et al (2013) identified constraints that this sub-segment must face when experiencing sport tourism.…”
Section: Travel Constraints For Tourists With Disabilitiesmentioning
confidence: 99%
“…These include young people, older people, those from black and minority ethnic communities and the disabled (see, for example, Banister and Bowling, 2004;Burnett and Baker, 2001;Davey, 2007;Delbosc and Currie, 2011;Giuliano, 2003;Hodgson and Turner, 2003;Jones et al, 2000;Schmöcker et al, 2008). In general such research is not explicitly framed around either access to work or low incomes per se, but given the nature of the groups certainly the latter often acts as an underlying factor.…”
Section: Transport Barriers By Social Groupsmentioning
confidence: 99%